Crenças sobre uma língua e cultura-alvo (alemã) em dimensão intercultural de ensino de língua estrangeira - Rozenfeld, Cibele Cecílio de Faria (2007)
In a historical overview of foreign language (FL) teaching, a pragmatic change can be observed starting in the 1970s, in which the emotional and affective aspects of the learners take on a relevant position. This change involves a shift not only in the teacher s role, which passes from that of centralizer, retainer and transmitter of knowledge to facilitator of the process, but also in that of the student, who is now seen to be inserted into a broader learning context and who has now gained the possibility of participating actively in the learning process. In this context, the belief system is perceived as a phenomenon inherent to the affective processes of teachers and/or students, which influences the teaching and learning process and is therefore a relevant factor. In this research of a qualitative nature and ethnographic basis, we sought to investigate and characterize the beliefs of German language students concerning the language and target culture, evaluating their possible origins and how they could be understood by the teacher in the FL teaching/learning process. To achieve these objectives, we sought theoretical backing in belief studies (Barcelos, 2004; Vieira-Abrahão & Barcelos, 2006; Almeida Filho, 1999; Horwitz, 1999 and others) and in assumptions of the interculturality of foreign language teaching and of the understanding of what is foreign (fremd) (Wierlacher, 1998; Weinrich, 1998; Kramsch, 1993; and others). We focused primarily on the concept of intercultural competence (Volkmann, 2002; Weier, 2002; Byram, 2000; and others), seeing it as a way to provide theoretical underpinnings to understand these issues. With this research, we hope to contribute to a better understanding of this construct (beliefs), which has been intensively investigated in the field of language teaching studies. In addition, we aim to provide teachers of German as a FL with critical reflections focusing on learners and on FL teaching as an intercultural practice.